Bis(mu-4-hydroxybenzoato-kappa O-2:O `)bis[triaquabis(4-hydroxybenzoato)-kappa O;kappa O-2,O `-terbium(III)] decahydrate - Zhu, Y.M.; Feng, P.P.; Yang, Y.Y.; Ng, S.W. (International Union of Crystallography, 2010)
The title dinuclear compound, [Tb-2(C7H5O3)(6)(H2O)(6)]center dot 10H(2)O, lies on a center of inversion and the two Tb-III atoms are bridged by two 4-hydroxybenzoate anions; each metal atom is further coordinated by one monodentate anion and chelated by the third anion. The eight-coordinate geometry approximates a square antiprism. Hydrogen bonds of the O-H center dot center dot center dot O type connect the uncoordinated water molecules to the dinuclear species, forming a three-dimensional network.